We were dreamers : an immigrant superhero origin story - Liu, Simu, 1989- (William Morrow, an imprint of HarperCollins Publishers, 2022)
"We Were Dreamers is the superhero origin story of Simu Liu, Marvel Cinematic Universe's first leading Asian superhero, who grew up torn between China and Canada, until he found the courage to dream like his parents before him. Witty, honest, inspiring and relatable, We Were Dreamers weaves together the narratives of two generations in a Chinese immigrant family who are inextricably tied to one another even as they are torn apart by deep cultural misunderstanding. Let's just say, it's really hard to be seen as cool amongst your peers when your parents assign you hours of extra homework every night. And it's similarly hard to admit to those parents, years later, not only that you've lost your respectable accounting job--the one they invested hundreds of thousands of dollars in to prepare you for--but also that you kinda want to be an actor. Going beyond his own experiences, Simu tells the story of his parents' decision to leave him behind to be raised by his grandparents while they sought a future in North America, and of the shock and loss he experienced when the father he hardly even remembered showed up one day to take him away from the only home he had ever known. He offers a no-holds-barred look at the struggles he and his parents experienced as they tried to become a family while dealing with culture gaps, racism and wildly conflicting definitions of success. And he shares many entertaining stories of his own incredible path to success, from the acting gigs he landed through Craigslist ads to dressing up as Spider-Man at kids' birthday parties and serving as Pete Wentz's stunt double on a Fall Out Boy music video. Ultimately, it is Simu's singular determination to make his dreams come true that not only leads him to succeed as an actor but also opens the door to reconciliation with his parents. For by the time he is thirty--the same age his parents were when they immigrated--he recognizes that he and his parents have much in common, most notably their courage to dream, and to dream big. We Were Dreamers is a story about growing up as a third-culture kid, about losing and finding family, and about making your own luck. More than one family's story, it is part of a larger narrative about Asian Canadian culture--a colorful and nuanced tale that is worthy of being told and deserving of a wide readership."--